Business intelligence cookbook : a project lifecycle approach using Oracle technology - Heaton, John (Packt Pub., 2012)
Over 80 quick and advanced recipes that focus on real world techniques and solutions to manage, design, and build data warehouse and business intelligence projects with this book and ebook.